Charge Prediction Machine: A tool for inferring precursor charge states of Electron Transfer Dissociation tandem mass spectra - Carvalho, Paulo C (2009)
Electron Transfer Dissociation (ETD) can dissociate highly charged ions. Efficient analysis of ions dissociated with ETD requires accurate determination of charge states for calculation of molecular weight. We created an algorithm to assign the charge state of ions often used for ETD. The program, Charge Prediction Machine (CPM), uses Bayesian decision theory to account for different charge reduction processes encountered in ETD, and can also handle multiplex spectra. CPM correctly assigned charge states to 98% of the 13,097 MS2 spectra from a combined dataset of four experiments. In a comparison between CPM and a competing program, Charger (ThermoFisher), CPM produced half the mistakes.